“Spiral stenting": creating a subintimal neo-luminal helix around a massively calcified ostial chronic total occlusion of the right coronary artery in a patient with recurrent ventricular tachycardia - Mashayekhi, Kambis; Akın, Ibrahim; Behnes, Michael (Journal of thoracic disease, 2016)
This case report describes a successful percutaneous coronary intervention (PCI) of a severely calcified aorto-ostial chronic total occlusion (CTO) of the right coronary artery (RCA). The lesion was treated by a retrograde approach implementing long spiral subintimal wire tracking and final coronary stenting creating a subintimal neo-luminal helix around the natively occluded RCA. After 6 months of follow-up valuable angiographic results were proven.
Gesehen am 12.06.2019